2015
DOI: 10.3899/jrheum.141520
|View full text |Cite
|
Sign up to set email alerts
|

Flare Rate in Patients with Rheumatoid Arthritis in Low Disease Activity or Remission When Tapering or Stopping Synthetic or Biologic DMARD: A Systematic Review

Abstract: Results suggest that more than one-third of patients with RA with LDA or in remission may taper or stop DMARD treatment without experiencing a disease flare within the first year. Dose reduction of TNF blockers results in lower flare rates than stopping and may be noninferior to continuing full dose. Radiological progression after treatment deescalation remains low, but may increase slightly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 30 publications
3
78
1
Order By: Relevance
“…Current evidence suggests that once remission has been achieved, treatment de-escalation may be considered,4 5 but most recent studies have focused on de-escalation of biological disease modifying anti-rheumatic drugs ((b)DMARDs) only 4…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that once remission has been achieved, treatment de-escalation may be considered,4 5 but most recent studies have focused on de-escalation of biological disease modifying anti-rheumatic drugs ((b)DMARDs) only 4…”
Section: Introductionmentioning
confidence: 99%
“…These differences might be explained by the fact that our meta-analysis includes 17 articles, 9 of which were not available when the Cochrane Library undertook its systematic analysis of the literature in September 2013. The results of another meta-analysis13 published in 2015 suggested that tapering or stopping bDMARDs was possible in more than one-third of patients in LDA or remission; however, there was a high level of heterogeneity due to the simultaneous inclusion of anti-TNF discontinuation studies and anti-TNF dose reduction studies, whether retrospective or prospective.…”
Section: Discussionmentioning
confidence: 99%
“…However, discontinuing anti-TNF was associated with worse functional and radiographic outcomes. Another systematic analysis of the literature,13 including 15 studies focused on various anti-TNF agents, assessed the occurrence of flare-ups at approximately 30% after discontinuing or tapering anti-TNFs.…”
Section: Introductionmentioning
confidence: 99%
“…Results from several studies suggest that biological treatment can be reduced to a half dose in patients in remission without an increased risk of flare 13,14 . In some patients, biological treatment may even be withdrawn completely 15,16 , although identification of these patients, based on clinical factors, is not yet possible. A second substantial cost reduction may be realized by switching patients to less-expensive biosimilars.…”
Section: Rheumatologymentioning
confidence: 99%